The Relationship Between Early Breastfeeding Initiation And Exclusive Breastfeeding - Nandini Parahita Supraba; Putri Rhadiyah; Rohmatun Karimah; Tesza Rezky Permata; Endriyani Martina Yunus (Institut Citra Internasional, 2026)
The low coverage of exclusive breastfeeding (53.93%) at the Kelapa Community Health Center risks increasing stunting rates, gastrointestinal infections, and neonatal mortality, considering that exclusive breastfeeding is a critical intervention in the first 1,000 days of life. Early Initiation of Breastfeeding (IMD), which coverage is only 65.75% in this area, has the potential to be the key to increasing the success of exclusive breastfeeding. The purpose of this study was to determine the relationship between Early Initiation of Breastfeeding (IMD) and exclusive breastfeeding. The research method used a cross-sectional analysis with a quantitative survey approach. A sample of 30 mothers was selected through purposive sampling. The instrument was a validated structured questionnaire. Data were analyzed using the chi-square test (α = 0.05) with the help of SPSS version 25. The results showed that IMD was associated with exclusive breastfeeding (p <0.05). A total of 21 respondents carried out IMD, 20 respondents provided exclusive breastfeeding (95.2%) and only 1 person (4.8%) who did not provide exclusive breastfeeding. The conclusion in this study is that IMD is related to exclusive breastfeeding, mothers who get the opportunity to IMD, their exclusive breastfeeding is successful. The impact of the study is that the success of exclusive breastfeeding is partly due to the mother getting the opportunity to IMD. Health workers are advised to always carry out IMD on new mothers.